Valorization of kenaf seeds as potential food ingredient with health benefits - Nevara, Gita Addelia; Syed Muhammad, Sharifah Kharidah; Zawawi, Norhasnida; Mustapha, Nor Afizah; Karim, Roselina (Iksad Publishing House, 2024)
Originating from kenaf seed, kenaf seed gum (KSG) is an innovative seed gum candidate. The health benefits of KSG were assessed in comparison to those of commercial guar gum (GG) and locust bean gum (LBG), with regards to their bio-functional and antioxidant properties. The cholesterol and bile salt binding capacities of KSG were 7.01 mg/g and 82.58% which were comparable to commercial seed gums. However, KSG revealed lower glucose absorption capacity compared to commercial GG and LBG. In addition, the antioxidant properties of the KSG were comparable to those of commercial seed gums, as measured by Ferric Reducing Antioxidant Power (FRAP) and DPPH radical scavenging activity. This research offers fundamental insights that can be utilized to investigate the potential of KSG as an unconventional seed gum, particularly in the food industry.